PTU-149 Is Pepsin Detected in the Saliva of Healthy Individuals?. (4th June 2013) - Hayat, J O; Woodcock, A; Dettmar, P; Yazaki, E; Kang, J-Y; Sifrim, D
Abstract : Introduction: The presence of pepsin in the oesophagus or more proximally (pharynx or airways) suggests gastro-oesophageal reflux (GOR). However, appropriate normal values and correlation with acid and non acid reflux are still limited. The aim of this study was to measure pepsin in expectorated saliva together with objective assessment of GOR by pH-impedance in a large cohort of healthy asymptomatic subjects. Methods: 100 healthy subjects, age 30.7 (range 19–55), BMI 23.7 (17.7–32.8) with no typical or atypical reflux symptoms underwent MII-pH monitoring "off" PPI. Oesophageal pH was measured 5 cm above the LOS and impedance sensors were positioned at 3.7.9.12 and 15 cm above LOS. Subjects collected expectorated saliva on waking, one hour after lunch and one hour after dinner. Saliva was collected into tubes containing 0.5 ml of 0.01 M citric acid and analysed for the presence of pepsin using a lateral flow test comprising two unique human monoclonal antibodies to pepsin (Peptest™, RDBiomed Ltd). The cut off value to determine pepsin positivity was 25 ng/ml. Results: Of 300 saliva samples tested, 19% were +ve for pepsin. 64% of subjects had all three saliva samples negative; 20% had 1 sample positive, 12% had 2 samples positive and 4% had 3 samples positive. A similar percentage of samples were positive after lunch (24%) and dinner (22%), but lower on waking (10%). Median acid exposure time was 0.3% (IQR – 0.1–0.8%, 95 th centile 3.5%). Median no. of reflux events was 32 (15–42, 77) being acid 11 (5–22.47) and non-acid 15 (8–25, 46). Saliva samples positive for pepsin were preceded by significantly more reflux events during the 60 min interval before sampling compared to negative samples both after lunch and dinner (+ve pepsin 6 reflux (4–9) vs. -ve pepsin 3 reflux (1–5) p < 0.0001). Supine acid exposure and no. of reflux episodes was not significantly different with +ve or -ve morning samples. Subjects with 3 saliva samples +ve for pepsin had a higher ratio of proximal reflux episodes than subjects with no +ve samples (37%(range 29–40%) vs. 19%(12–33%), p < 0.02). Only 6/300 samples contained more than 250 ng/ml pepsin. Conclusion: Pepsin was found in the expectorated saliva of a proportion of healthy individuals who did not experience reflux symptoms, particularly post-prandially. However, only 4% of healthy subjects had 3 positive samples. An increased number of reflux episodes were found prior to giving saliva samples with detectable levels of pepsin. Our results suggest that the presence of pepsin in saliva can be a potential screening tool for GERD when at least 3 samples throughout a day are positive or samples contain more than 250 ng/ml pepsin. Disclosure of Interest: None Declared